Effectiveness of Progressive Muscle Relaxaion Technique on Pain among Cancer Patients Receiving Radiation Therapy - Pavendan, K.; Manimozhi, R.; Bai, R. Regi (Indian Journal of Nursing Sciences, 2024)
Background: Pain in cancer may arise from a tumor compressing or infiltrating nearby body parts; from treatments and diagnostic procedures; or from skin, nerve, and other changes caused by a hormone imbalance or immune response. Progressive muscle relaxation technique, a complementary approach to pain relief, is a form of body work that focuses primarily on the feet. Methodology: A quasi-experimental study was conducted to evaluate the effectiveness of progressive muscle relaxation technique on pain among cancer patients receiving radiation therapy. Totally, 60 samples were selected by non-probability purposive sampling technique, among them, 30 were in the experimental group and 30 samples were in the control group. The investigator implemented progressive muscle relaxation technique for 15 days with the duration of 20–30 min. The level of pain was assessed using numerical pain intensity rating scale. The data gathered were analyzed by descriptive and inferential statistical method. Results: The finding revealed that, in the experimental group, the post-test mean score was 4.10 ± 1.63 and, in the control group, the mean score was 7.13 ± 2.11 with the mean difference of 3.03. The independent “t”-test value (t = 6.23) is highly significant. The paired “t”-test value (t = 8.24) revealed that progressive muscle relaxation technique was effective in reducing the pain. In the experimental group, there is a significant association found between the post-test level of pain and the variables such as age (χ² = 9.47), occupational status (χ² = 12.44), and stage of cancer (χ² = 9.83). Conclusion: The progressive muscle relaxation technique was effective in reduction of pain among cancer patients receiving radiation therapy.